The Influence of AI-Enabled Predictive Analytics on ERP-Based Strategic Planning in Defense Supply Chains - Atakari, Chandrasekhar (International Journal of Emerging Research in Engineering and Technology, 2025)
The contemporary defense supply chain forms an extremely intricate and mission-critical environment, which necessitates an heretofore unseen degree of resilience, promptness, and vision. Enterprise Resources Planning (ERP) systems have, over the years, been used as a backbone in defense logistics and planning, but with Artificial Intelligence (AI) - enabled predictive analytics in play, it has changed the landscape of strategic planning within these systems. The study will examine how predictive analytics using AI will improve the strategic planning of defense supply chains using ERP. The study provided by the synthesis of the case studies, simulation models, and statistics will show that the AI-based predictive modules can considerably help enhance decision-making accuracy, minimize supply risks, and optimize the inventories. The suggested framework uses machine learning algorithms, real-time data feeds, and ERP systems to anticipate fluctuation in the demand, create a schedule for maintenance, and reduce supply chain vulnerabilities. The results lead to the conclusion of measuring up to 35 percent of the increase in operations readiness and 27 percent fewer logistical delays occurring in the tested defense supply ecosystems. A comparative image of the regular ERP systems and the AI-driven ERP models is also examined in the paper. An organized approach, which integrates data-based models, Monte Carlo simulations, and system dynamics modelling, is employed. Findings demonstrate the crucial importance of AI predictive analytics in helping prevent disturbances such as geopolitical crises, cyber threats, and supplier failure. There is a policy implication of the discussions on the stakeholders in defense, such as NATO, the U.S. DoD, and the allies, that should consider implementing AI-based ERP systems. The given study has its academic and practical value, proposing a strategic framework specific to defense logistics and providing recommendations regarding the studies that are yet to be conducted on the topic of secure, explainable, and adaptive AI in ERP systems